EDUKASI TANGGAP BENCANA BAGI TIM RELAWAN KESEHATAN STIKes DHARMA HUSADA UNTUK SIAP SELAMAT MENGHADAPI BENCANA - Sophiana Sukma, Alisa; Daryaman, usan; Suparni, Suparni (Jurnal Sehat Masada, 2024)
The role of health workers in disaster management preparedness in the pre-disaster phase by providing information related to strategies that can be carried out both for disaster preparation and response, including the implementation of health training and education to increase knowledge of community preparedness to face disasters regarding the main indicators of preparedness knowledge to measure the readiness of volunteer workers consisting of medical, non-medical personnel, community leaders and government assistance for disasters. STIKes Dharma Husada Bandung is a health campus that is engaged in disaster volunteering by implementing the Tri Dharma College of Education, Research, and Community Service. STIKes Dharma Husada Bandung has a Health Team Student Activity Unit which one of its main tasks and functions is to work in the field of disaster volunteers before providing assistance in the event of a disaster must have sufficient knowledge. This study aims to determine the effect of flood disaster response health education on the knowledge of members of the STIKes Dharma Husada Bandung HEALTH TEAM for the period 2021-2022. The type of research used was Quasi Experimental with pre and posttest without control with a Cross Sectional approach with a total sample of 44 people. Data analysis used univariate and wilxoco test with the results of the study showing that 18 respondents (40.9%) had good knowledge, 24 respondents (54.5%) had sufficient knowledge and 2 respondents (4.5%) lacked knowledge and 39 post-pendidikan kesehatan knowledge. respondents (88.6%) have good knowledge, 5 respondents (11.4%) have sufficient knowledge and 0 respondents (0%) lack knowledge. There is a significant effect between before and after health education on flood disaster response (p-value=0.000). It is hoped that members of the Health Team will be able to participate in training to improve flood disaster response as a provision to become volunteers in the event of a disaster.